TUBERCULIN SKIN TESTING SURVAY - J. Feiz; M. Miralai; F. Sohrabi (Tehran University of Medical Sciences, 1976)
The tuberculin skin test is the most effective means for detecting tuberculosis. Therefore, it is an essential tool in epidemiological surveys for control and ultimate eradication of tuberculosis. The estimate the rate of tuberculosis infection (Mycobacterium tuberculosis) and prevalence of mycobacterium other than Mycobacterium tuberculosis, so called atypical mycobacterium, in IRAN 920 army men, ranging in age from 18-26 years, who have been born and lived in different part of Iran were skin tested. Every individual received two intradermal injections (Mantoux test). One with 5 tuberculin units of PPD-S, prepared from Mycobacterium tuberculosis. The other was 5 tuberculin units of PPD-G, prepared from Scothchromogenic Mycobacterium. 343 individuals (43.5%) of total number tested showed a positive reaction (10mm or more indurations) to PPD-S. The size of the reaction to PPD-G of 222 individuals (28.3%) of total number was more than the size of reaction to PPD-S. This latter I group seems to have been infected with atypical mycobacterium. Alth.dug14. the distribution of individuals tested doesn't correspond with the population of each area, but, everyone entered in this study has been appointed at random to the Isfahan military base. This study demonstrates that atypical mycobacterium infection is present in all provinces of Iran and tuberculin reactors are highest in north provinces an extensive epidemiological study in different parts of Iran in this connection is suggested. In this paper the source of low grade sensitivity to PIPD-S observed above and the significance of cross reaction in epidemiological survey of tuberculosis has been discussed in detail.